2021
DOI: 10.1186/s13568-021-01326-1
|View full text |Cite
|
Sign up to set email alerts
|

Metarhizium robertsii protease and conidia production, response to heat stress and virulence against Aedes aegypti larvae

Abstract: Nutritional factors exert significant influence on the growth of entomopathogenic fungi, one of the main agents employed commercially in the biological control of arthropods. Thus, the objective of this work is to optimize the culture medium and solid fermentation time for production of proteases and conidia of Metarhizium robertsii ARSEF 2575 and to evaluate the interference of riboflavin and salts on virulence and resistance to abiotic stress factors. In the first step, nine groups were separated: negative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…4 b). Comparably, Ferreira et al ( 2021 ) showed that culture medium supplemented with sodium nitrate and riboflavin enhanced protease activity and conidia production of Metarhizium robertsii . Similarly, additives such as soybean protein combined with wheat bran induced the protease activity of M. anisopliae (Kim et al 2020 ), and the supplementation with yeast extract improved the chitinase composition of M. anisopliae (Dhar and Kaur 2009 ).…”
Section: Resultsmentioning
confidence: 93%
“…4 b). Comparably, Ferreira et al ( 2021 ) showed that culture medium supplemented with sodium nitrate and riboflavin enhanced protease activity and conidia production of Metarhizium robertsii . Similarly, additives such as soybean protein combined with wheat bran induced the protease activity of M. anisopliae (Kim et al 2020 ), and the supplementation with yeast extract improved the chitinase composition of M. anisopliae (Dhar and Kaur 2009 ).…”
Section: Resultsmentioning
confidence: 93%
“…Most of the scientific papers deal with the use of SSF to grow fungi and oomycetes ( Supplementary Table S1 , Refs. [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , …”
Section: Solid-state Fermentation For Biopesticides Productionmentioning
confidence: 99%